Influence of inorganic scintillator light output non-proportionality and energy of registered ionizing radiation on radiometric parameters of detectors on their base - Viday, Yu.T.; Tarasov, V.A.; Gorbacheva, T.E. (Functional Materials, 2008)
The effect of the non-proportionality in light yield and the radiation energy on the radiometric characteristics of thallium-doped cesium iodide detectors and p-terphenyl ones. The increase of the non-proportionality in the energy and light yield at the recording of 5 MeV and 2 MeV a-particles has been shown to result in an increased background counting rate, decreased detector sensitivity and resolution. These changes in radiometric parameters are influenced significantly by the state of the radiation input surfaces of the Csl(TI) and p-terphenyl detectors. Розглянуто вплив непропорційності світлового виходу та енергії випромінювання при реєстрації низькопроникного випромінювання на радіометричні характеристики детекторів на основі йодіду цезія, активованого талієм, та на основі п-терфенілу. Показано, що збільшення непропорціональності світлового виходу та енергії при реєстрації а-частинок з енергіями 5 МеВ і 2 МеВ приводить до збільшення фонової швидкості рахування, зменшення чутливості детектора та його роздільної здатності. На ці зміни радіометричних параметрів суттєвий вплив чинить стан вхідної для випромінювання поверхні сцинтиляторів СsІ(ТІ) та п-терфенілу. Рассмотрено влияние непропорциональности светового выхода и энергии излучения при регистрации малопроникающего излучения на радиометрические характеристики детекторов йодистого цезия, активированного таллием, или на основе п-терфенила. Показано, что увеличение непропорциональности светового выхода и энергии при регистрации а-частиц с энергиями 5 МэВ и 2 МэВ приводит к увеличению фоновой скорости счета, уменьшению чувствительности детектора и его разделяющей способности. На эти изменения радиометрических параметров существенное влияние оказывает состояние входной для излучения поверхности сцинтилляторов Csl(ТJ) и п-терфенила.